1989
DOI: 10.1111/j.1432-1033.1989.tb14938.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism of Escherichia coli studied by Mössbauer spectroscopy and biochemical methods

Abstract: To date it has barely been recognized that the nature of about 75% of the Escherichiu coli iron pool is unknown. Here we report the isolation of two iron species representing major components of iron metabolism in various growth states of E. coli. In vivo Mossbauer spectroscopy was applied to obtain information on the intracellular distribution pattern of iron in E. coli K12 W3110. Only two types of iron could be detected in the cell spectra: hexacoordinated Fe2+ and Fe3 + high-spin complexes. Other iron-requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
29
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 43 publications
7
29
0
Order By: Relevance
“…However, in overloaded cells, Bfr iron represents a very low proportion of the total iron content, and low molecular mass molecules carry the bulk of the cellular iron content and fulfill the iron storage function. These results are supported by studies performed on E. coli in which Bfr iron was shown to represent no more than 1% of the total cellular iron, the bulk of iron in the iron-rich cells being in the form of aggregates (42,43).…”
Section: Discussionmentioning
confidence: 58%
“…However, in overloaded cells, Bfr iron represents a very low proportion of the total iron content, and low molecular mass molecules carry the bulk of the cellular iron content and fulfill the iron storage function. These results are supported by studies performed on E. coli in which Bfr iron was shown to represent no more than 1% of the total cellular iron, the bulk of iron in the iron-rich cells being in the form of aggregates (42,43).…”
Section: Discussionmentioning
confidence: 58%
“…In several studies one of us (B.F.M.) has demonstrated that M6ssbauer spectroscopy of whole cells yields valuable information about the major components of iron metabolism as well as their time-dependent changes [16][17][18]. All of this has been done without the need for interference from any isolation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…and Matzanke et al,6) however, reported that in E. coli, bacterioferritin iron represents no more than 1% of the total iron and most of this metal in cells was the form of aggregates, which could be associated with a novel form of iron-protein. More recently, Laurehere et al 7 ) have shown that most iron in a strain of cyanobacterium was associated with a low-molecular-mass compound « 10 kDa), which fulfilled the storage function.…”
mentioning
confidence: 98%